Productive characteristics and physiological potential of sunflower acheneâs a function of spatial arrangement of plants and the cultivation area - Francisco Thiago Coelho Bezerra (2013)
Sunflower crop is becoming significant in the national and international scene, mainly due to the possibility of the use of oil for biodiesel production. Thus, the present study aimed to evaluate spatial arrangements and local culture on vegetative characteristics, yield components, yield and physiological potential of sunflower acheneâs variety of Embrapa 122. The regions were at the Experimental area from Department of Plant Science, in Fortaleza, CE, and at Experimental Farm Vale do Curu, in Pentecost, CE. Treatments consisted of combinations of row spacingâs (0.30, 0.50, 0.70 and 0.90 m) and planting densities (30,000, 45,000, 60,000 and 75,000 plants per hectare) in a factorial 4 x 4, totaling 16 treatments arranged in four randomized blocks. These characteristics were stem diameter at soil level, stem length, number of leaves, leaf area, leaf area index, chapters collected, head diameter, mass chapter, mass of seeds for each chapter, mass of 100 seeds, acheneâs per chapter, achene yield, harvest index and oil content in the acheneâs. Physiological acheneâs was evaluated by germination and vigor (first germination count, electrical conductivity, accelerated aging, seedling emergence and shoot length and root and dry weight of shoots and roots of seedlings emergency test). The experiments were analyzed together in relation to the growing cultivation site, the data were submitted to variance analysis and quantitative factors tested by regression using the F test (p <0.05) to check the adjustment to models. The spatial arrangements providing greater intraspecific competition affect the vegetative characteristics, reduce yield components and physiological acheneâs, but not affect productivity. The growing place was the factor that most influenced the vegetative characteristics, yield components and achene production, mainly due to irregular and low rainfall. Germination and vigor of acheneâs were also affected by growing place, the differences may be related to the maturation process caused by climatic factors.